Faecal contamination and its relationship with some environmental variables of four urban rivers in inner Hanoi city, Vietnam - Le Nhu, Da; Nguyen Thi Mai, Huong; Hoang Thi Thu, Ha; Duong Thi, Thuy; Phung Thi Xuan, Binh; Pham Thi Mai, Huong; Pham Thi Minh, Hanh; Le Thi Phuong, Quynh (Vietnam Journal of Earth Sciences, 2023)
Coliform bacteria are essential variables for assessing riverine water quality. In this study, the faecal indicator bacteria (FIB) in relationship with some physico-chemical variables were investigated during the period 2020-2022 for four urban rivers (To Lich, Lu, Set, and Kim Nguu) in the inner Hanoi city to provide the updated water quality of these rivers. The results demonstrated severe faecal coliforms contamination in riverine waters compared to the permissible values of the Vietnam technical regulation for surface water quality, QCVN08-MT:2015/BTNMT column B1. Nutrients (ammonium and phosphate) concentrations and dissolved oxygen (DO) values exceeded the permissible values, whereas pH was within the standard. The Pearson analysis demonstrated the significant positive correlation between total coliforms (TC) and Escherichia coli (EC) densities and ammonium concentration in the riverine water. Besides, these variables were higher in the dry season than the rainy one for all sites observed. All these reflect the critical role of the point sources, notably domestic wastewater inputs in the four river basins. Considering these rivers' deteriorating condition, developing an effective wastewater treatment system is necessary for the rivers in Hanoi.